PENERAPAN GAMIFIKASI STRUKTURAL UNTUK MENINGKATKAN MINAT BELAJAR IPAS SISWA KELAS IV SD NEGERI 6 WATAMPONE KABUPATEN BONE - Jauhar, Sitti; Kadir, Abd; Indah Sari, Andi Nur (MACCA : Science-Edu Journal, 2025)
This research is motivated by the Application of Structural Gamification to Increase Interest in Learning IPAS Class IV Students of SD Negeri 6 Watampone, Bone Regency. The purpose of this study was to increase students' interest in learning by applying Structural Gamification in IPAS class IV SD Negeri 6 Watampone, Bone Regency. This type of research is Classroom Action Research (PTK) conducted in class IV SD Negeri 6 Watampone with a total of 35 students. The data collection techniques used were observation and questionnaire. The data analysis technique used was descriptive qualitative which was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that there was an increase in students' IPAS learning interest from cycle I which was included in the medium qualification with a percentage of 68% to high qualification with a percentage of 89% in cycle II. Thus it can be concluded that the application of Structural Gamification can increase the interest in learning IPAS of fourth grade students of SD Negeri 6 Watampone.